Case Study on Road Safety Analysis in the Area of Educational Units - A.P. Tuliga; C. Coman; C. Plescan; V. Batranu-Pintea (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2022)
The article addresses the topic of road safety in the area of educational units, respectively the effect of road traffic. The aim of the study is to clearly highlight the causality between road accidents involving children as victims and road systematization. To achieve our main objectives, we used as a research method the analysis of documents: Road Accident Database, an application of the Romanian Police in which all traffic incidents registered in Romania are implemented, according to the criteria of Mehedinti County, student quality, road category (national, county, communal), the location of the school unit in the vicinity of the public road and the production of the traffic incident. One of the factors that decisively influences the quality of road traffic, therefore, implicitly the risk in traffic, is the public road network. The specialized studies, as well as the available international statistics, show that the main categories exposed to the risk of road accidents resulting in deaths and serious injuries are: pedestrians, cyclists, motorcyclists and mopeds, in other words, the category known in specialized practice as "the most vulnerable traffic participants”.